(اللغة العربية آلة لفهم القرآن (دراسة تحليلية في القرآن الكريم سورة الزخرف الآية 3 - Ghofur, M. Abdul (UAS PRESS, 2018)
This study is intended to explore the contents of the letter az-zukhruf verse 3 which discusses the Al-quran derived in Arabic and Arabic as a tool / tool for learning the Qur’an. There are things that make it possible to provide information about existing content and provide bene????its to writers and readers. This study uses a descriptive method with a qualitative approach. The subject of the study is the Qur’an Surat Az-zukhruf verse 3. The results of this study that these verses have several views and interpretations of the scholars’ interpreters who can be used for the Qur’an. The Qur’an is derived by using beautiful and complete language with meaning.